Professionally Important Qualities and Professional Achievement Among Inspectors in the State Small Vessels Inspectorate of EMERCOM of Russia - Julia S. Shoigu; Anastasia А. Tarasova (Rossijskij psihologičeskij žurnal., 2018)
Introduction. This paper continues a previous study on professionally important qualities of inspectors in the State Small Vessels Inspectorate (SSVI) of EMERCOM of Russia. Professionally important qualities contribute to professional achievement among inspectors in the SSVI of EMERCOM of Russia. This is a prerequisite for a unitary methodological approach to the selection of a candidate for a position of an inspector in the SSVI of EMERCOM of Russia. The aim of the study is to determine the relationships among professionally important qualities of inspectors in the SSVI of EMERCOM of Russia and professional achievement among the surveyed specialists. Methods. An expert survey and statistical treatment of data helped to measure professional achievement. The survey revealed assessments of professional achievement for each participant. An integral expert assessment was an external criterion for professional achievement among inspectors in the SSVI of EMERCOM of Russia. Results. The results indicated that professionally important qualities of inspectors in the SSVI of EMERCOM of Russia determined their professional achievement. At the same time the whole complex of professionally important qualities promoted more effective performance of professional activities. Discussion. The previously revealed professionally important qualities can predict professional achievement among inspectors in the SSVI of EMERCOM of Russia. The findings can be readily used in professional psychological selection for the position of an inspector in the SSVI of EMERCOM of Russia in order to reduce negative psychological consequences, psychosomatic and other diseases associated with professional activities.